2020
DOI: 10.2106/jbjs.st.19.00067
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Sacroiliac Joint Fusion

Abstract: Background: Minimally invasive sacroiliac (SI) joint fusion is indicated for low back pain from the SI joint that is due to degenerative sacroiliitis and/or sacroiliac joint disruption. This technique is safe and effective in relieving pain uncontrolled by nonoperative management 1 - 4 . There is some controversy, but there continues to be increasing evidence of effectiveness. Description: This procedure is performed, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Both cohorts demonstrated improvement in outcomes throughout the follow-up period 48. A major possible complication of MI SI joint fusion is nerve damage of L5-S2, often because the implant was malpositioned 49. Consequently, nerve impingement is a common indication for revision surgery 49.…”
Section: Treatmentmentioning
confidence: 95%
See 2 more Smart Citations
“…Both cohorts demonstrated improvement in outcomes throughout the follow-up period 48. A major possible complication of MI SI joint fusion is nerve damage of L5-S2, often because the implant was malpositioned 49. Consequently, nerve impingement is a common indication for revision surgery 49.…”
Section: Treatmentmentioning
confidence: 95%
“…48 A major possible complication of MI SI joint fusion is nerve damage of L5-S2, often because the implant was malpositioned. 49 Consequently, nerve impingement is a common indication for revision surgery. 49 One retrospective study of robotic guidance and neuronavigation suggested improved accuracy of percutaneous screw placement compared with fluoroscopic guidance.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The EQ-5D is a 5-item questionnaire that measures health-related quality of life based on five dimensions of health: mobility, self-care, daily activities, pain/discomfort and anxiety/depression (76). Patients can use the dimensions to delineate to what extent they experience problems, scoring from 1 (no problems) up to 5 (extreme problems).…”
Section: Euroquol-5d (Eq-5d)mentioning
confidence: 99%
“…Compared to 2D-assisted conventional techniques, there is subsequent evidence that 3D-assisted techniques can reduce screw malposition rate (73), operating time (73)(74)(75) and fluoroscopy frequency (75). Moreover, promising outcomes of long lasting effects of decreased pain, reduced disability as well as increased daily function and improved QoL in patient that require SI joint fusion can be expected (76). Also, 3D-fluoroscopy can possibly suffice as a post-operative control examination with accuracies similar to that of post-operative CT (72,77), reducing radiation exposure to the patient.…”
Section: Part Iii: a Glance Into The Future: Treatment Improvementmentioning
confidence: 99%